Defence counsel's participation in a special pre-trial investigation of criminal offenses - S. Ye. Ablamskyi (Law and Safety)
The article is devoted to the issues related to the peculiarities of the defence counsel's participation in the special pre-trial investigation of criminal offenses. The following methods of scientific knowledge such as statistical, bibliographic, comparative law, forecasting and modeling were used during the research. Attention has been focused on the fact that the introduction of the procedural institute of special pre-trial investigation of criminal offenses is designed to ensure the inevitability of criminal liability for the committed criminal offence. Based on a systematic analysis of the current CPC of Ukraine dated 2012, the features of both special criminal proceedings in general and the participation of defence counsel in it have been outlined. It has been established that the role of defence counsel in this case is of special importance, because during special criminal proceedings it is very important to implement one of the basic principles of criminal proceedings, which is to ensure the right to defence, which is a state guarantee of rights, freedoms and legitimate interests of the suspect (accused). However, during the implementation of criminal procedural norms, which regulate the participation of defence counsel in special criminal proceedings, a number of problematic issues arise in connection with legislative inconsistencies. These include inconsistent provisions of the law on the initial moment of involvement of a defence counsel in a special pre-trial investigation, imperfection of the procedural mechanism for engaging a defense counsel, whose participation is mandatory when considering a request of an investigator or prosecutor for a special pre-trial investigation. to the regional centers of secondary legal aid, assessment of the services quality and proper performance by a lawyer who provides free of charge to the suspect (accused), his or her responsibilities, the possibility of replacing a lawyer, and another problems. Taking into account the study of judicial practice, doctrinal sources and decisions of the European Court of Human Rights some proposals to eliminate the outlined issues have been made.